Study of six patients with complete F9 deletion characterized by cytogenetic microarray: role of the SOX3 gene in intellectual disability. (17th September 2016) - Jourdy, Y.; Chatron, N.; Carage, M.‐L.; Fretigny, M.; Meunier, S.; Zawadzki, C.; Gay, V.; Negrier, C.; Sanlaville, D.; Vinciguerra, C.
Abstract : Essentials Some hemophilia B (HB) patients with complete F9 deletion present with intellectual disability (ID). We delineate six F9 complete deletions and investigate genotype/phenotype correlation. We identify SOX3 as a candidate gene for ID, acting through haploinsufficiency, in HB patients. All complete F9 deletions in ID patients should be explored with cytogenetic microarrays. Summary: Background: Large deletions encompassing both the complete F9 gene and contiguous genes have been detected in patients with severe hemophilia B (HB). Some of these patients present other clinical features, such as intellectual disability (ID). Objectives/Methods: In this study, we characterized six unrelated large deletions encompassing F9, by cytogenetic microarray analysis (CMA), to investigate genotype/phenotype correlation. Results: Five of the six patients included in this study presented with ID associated with HB. CMA showed that the six large deletions, ranging in size from approximately 933 kb to 9.19 Mb, were located within the Xq26.3 to Xq28 bands. In all cases, the complete deletion of F9 was associated with the loss of various neighboring genes (5–28 other genes). The smallest region of overlap for ID was a 1.26‐Mb region encompassing seven OMIM genes ( LOC389895, SOX3, LINC00632, CDR1, SPANXF1, LDOC1, SPANXC ). SOX3, our candidate gene for ID, encodes an early transcription factor involved in pituitary development. All of the patients studied who had both HB and ID had deletion of the SOX3 gene. Conclusions: All HB patients with an atypical phenotype, especially if complete deletion of F9 is suspected, should be referred to a geneticist for possible pangenomic assessment, because haploinsufficiency of genes flanking F9, such as SOX3 in particular, may result in a broader phenotype, including ID. Such assessment would be of particular value for the genetic counseling of female carriers with F9 deletions, as it would facilitate analysis of the risk of transmitting HB associated with ID.